Vascular surgery cases, questions and commentaries - Geroulakos, George (Springer)
This updated and revised second edition of Vascular Surgery: Cases, Questions and Commentaries provides a thorough overview of the management principles of clinical cases in vascular surgery. It also summarizes all the relevant topics the vascular trainee is expected to be familiar with. With an international panel of contributors, many of whom are also examiners on the UK, European or American Boards in Vascular Surgery, this book familiarizes the reader quickly with day-to-day clinical practice. Case presentations are presented in question-and-answer format and have been widely referenced to reassure the reader that the contents are established best practice. Most cases are accompanied by multiple x-rays or color illustrations for visual clarity. This book serves as a teaching resource for vascular trainees or practitioners who are reviewing for the oral board exam or practitioners who wish to refresh their expertise with an interactive source of information. It also provides established practitioners the wherewithal to review the current standards of practice in vascular surgery. Arterial aneurysms - Preoperative cardiac risk assessment and management of elderly men with an abdominal aortic aneurysm - Abdominal aortic aneurysm - Endoluminal treatment of infrarenal abdominal aortic aneurysm - Ruptured abdominal aortic aneurysm - Thoracoabdominal aortic aneurysm - Aortic dissection - Popliteal artery aneurysm - Renal artery aneurysm - Anastomotic aneurysms - False aneurysm in the groin following coronary angioplasty - Acute ischaemia - Acute thrombosis - Arterial embolism - Blast injury to the lower limb - Endoluminal treatment of traumatic arteriovenous fistula of the axillary artery - Management of chronic ischaemia of the lower extremities - Cardiovascular risk factors and peripheral arterial disease - Angioplasty for critical arterial stenosis - Lower limb claudication due to iliac artery occlusive disease - Erectile dysfunction due to aortic disease - Bypass to the popliteal artery - Chronic critical limb ischemia - Popliteal artery entrapment - Adventitial cystic disease of the popliteal artery - The obturator foramen bypass - Diabetic foot - Surgery of the major branches of the infradiaphragmatic aorta - Chronic visceral ischaemia - Acute mesenteric ischaemia - Renovascular hypertension - Management of portal hypertension - Management of portal hypertension - Management of extracranial cerebrovascular disease - Management of patients with carotid bifurcation disease - Carotid endarterectomy and cranial nerve injuries - Paragangliomas of the head and neck - Vertebrobasilar ischemia: embolic and low-flow mechanisms - Neurovascular conditions of the upper extremity - Neurogenic thoracic outlet syndrome - Thoracoscopic sympathectomy - Acute axillary/subclavian vein thrombosis - Raynaud’s phenomenon - Prevention and management of complications of arterial vascular surgery - Aortofemoral graft infection - Aortoenteric fistulas - Vascular access. The optimal conduit for hemodialysis - Acute ischaemia of the upper extremity following graft arteriovenous fistula - Amputations - Amputation in an ischaemic limb - Congenital vascular malformation - Management of venous disorders - Deep venous thrombosis - Primary varicose veins - Venous ulcers associated with deep venous insufficiency - Venous ulcers associated with superficial venous insufficiency - Iliofemoral venous thrombosis - Iliofemoral deep venous thrombosis (during pregnancy) - Lymphoedema - Management of upper extremity lymphoedema with microsurgical lymphovenous anastomosis - Management of upper extremity lymphoedema with liposuction.